(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Founded in 1967 the State Museum of Musical Culture of Azerbaijan has passed almost 60-year history, accumulated in its funds more than 63 thousand units of storage, became an important and active figure in the cultural life of Azerbaijan, transformed into a museum association of musical profile, as on its basis were created and successfully function as a whole several memorial museums - its branches. Scientific research, scientific-popularisation work, exhibition and concert activities are carried out in Azerbaijan and abroad. All this deserves and requires illumination and scientific generalisation, as well as 45 years of service to the Museum by its head.